The Influence Of Leadership Style And Organizational Culture On Employee Performance at BKPSDM Office, Malang City - Finsensia Remia; Willy Tri Hardianto; Setyaningrum, Fitria (International Research & Development for Human Beings (IRDH), 2025)
Human resources play a crucial role in an organization, as achieving organizational goals would be challenging without a strong and healthy workforce. To enhance employee performance, organizations must consider several factors, including leadership style, organizational culture, and employee motivation (Bangun W., 2012). This study aims to examine the impact of leadership style on employee performance and the influence of organizational culture on employee performance at the Malang City BKPSDM Office. The findings reveal that leadership style has a positive and significant effect on employee performance. Additionally, organizational culture also significantly contributes to improving employee performance. A combination of an effective leadership style and a conducive organizational culture fosters a productive work environment and enhances employee motivation. The study implies that management should adopt appropriate leadership strategies and strengthen organizational culture to maximize employee performance effectively.